Curries and spicy dishes for your slow cooker - Kris Dhillon (Rightway, an imprint of Constable & Robinson, 2011)
Readers have praised Kris Dhillon's 'The Curry Secret' for over 20 years. Now she shows how easily you can produce your favourite spicy and curry dishes in a slow cooker. Her collection of tasty recipes includes dishes from India, Thailand, Vietnam, Indonesia, Malaysia, Burma, Jamaica and North Africa.